PEMBINAAN RELIGIUSITAS MELALUI INTEGRASI PEMBIASAAN HARIAN DAN PESANTREN LIBURAN DALAM BUDAYA SEKOLAH KEJURUAN - Elysa Nurul Qomaria; Nikmawati Nikmawati; Nurul Lailiyah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This article aims to examine the effectiveness of integrating daily habits and holiday boarding school programs in shaping the religious character of students at SMK YPM 14 Sumobito Jombang. The background of this study is the moral and spiritual challenges faced by the younger generation in the digital age, which requires the strengthening of religious character education in vocational schools. The research method used is a qualitative approach with case studies through participatory observation, in-depth interviews, and documentation. The results show that daily habits such as congregational dhuha prayers, recitation of Asmaul Husna, and istighosah consistently instill the values of honesty, responsibility, and discipline. Meanwhile, the holiday boarding school program provides an intensive spiritual experience that strengthens the internalization of religious values and character transformation in students. The synergy between routine habits, periodic programs, and a consistent school culture, supported by the exemplary behavior of teachers and the participation of all school members, has proven effective in shaping a strong religious character. This integrative model can be an inspiration for other schools in building the spiritual character of students amid the challenges of the digital age and the moral crisis of the younger generation.